Hospitalisation for mental health disorders in Australians with type 1 or type 2 diabetes. (February 2023) - Tomic, Dunya; Morton, Jedidiah I.; Salim, Agus; Lambert, Tim; Magliano, Dianna J.; Shaw, Jonathan E.
Abstract: Aims: To determine the burden and leading reasons for mental health hospitalisation among Australians with diabetes. Methods: We determined the incidence of hospitalisation for all mental health disorders in people with type 1 or type 2 diabetes of all ages by linking the National Diabetes Services Scheme to hospital admission datasets from 2010 to 2017. We compared those with type 2 diabetes aged 15 and above to the general population using excess hospitalisations per 100, 000 person-years associated with diabetes. Results: Depressive disorders were the leading reason for mental health admission in Australians with diabetes, responsible for 6.09 (95% CI 5.78–6.42) and 7.05 (6.95–7.14) admissions per 1, 000 person-years in those with type 1 and type 2 diabetes, respectively. When considering only one admission per person, mental health admission rates were up to 90% lower. Among males with type 2 diabetes, stress and adjustment disorders were the leading cause of excess admissions compared to the general population, while depressive disorders were the leading cause in females. Conclusions: We found a substantial burden of psychiatric hospitalisations among Australians with diabetes, reinforcing the importance of mental health awareness among diabetes clinicians, and support by psychiatric teams for those with diabetes to prevent readmission.